Impact of obesity severity on postoperative outcomes and recovery progress in patients undergoing unilateral biportal endoscopy for degenerative lumbar disc herniation - Xu, Xiulei; Li, Jun; Song, Jie; Zhou, Gang; Cai, Jiren; Zhang, Xiaorui (Frontiers in Surgery, 2025)
BackgroundObese patients undergoing Unilateral Biportal Endoscopy (UBE) surgery for degenerative lumbar disc herniation may experience postoperative recovery significantly influenced by the degree of obesity and related factors. This study aims to evaluate the impact of obesity severity on postoperative complications and recovery progress following UBE surgery and to identify key intervention points.MethodsPreoperative baseline characteristics and postoperative follow-up data of patients with mild, moderate, and severe obesity were collected to analyze the incidence of complications, postoperative recovery trajectories, and key influencing factors. Multivariate logistic regression was conducted to examine factors affecting early mobilization (within 24 h), length of hospital stay, and anesthesia recovery time. Generalized linear mixed models (GLMM) were utilized to assess longitudinal changes in postoperative pain, functional disability, walking capacity, and muscle strength over time and their interactions with body mass index (BMI).ResultsObesity severity was significantly associated with the incidence of postoperative complications. Multivariate logistic regression analysis identified BMI classification, disc calcification, lumbar spondylolisthesis, and inflammatory markers as independent predictors of functional recovery, hospital stay, and anesthesia recovery time. Obese patients showed delayed functional recovery at the 3-month follow-up. Greater obesity severity was associated with slower improvements in walking ability at 1 and 3 months postoperatively. Moreover, obesity severity demonstrated a significant negative correlation with electromyographic activity at 1 month postoperatively.ConclusionObesity severity, inflammation, and anatomical factors are critical determinants of functional recovery in obese patients following UBE surgery. Patients with higher levels of obesity tend to have poorer mid- to long-term outcomes after UBE surgery. For such patients, enhanced postoperative mid- to long-term rehabilitation and physical function recovery are necessary to improve the prognosis of UBE.